Adsorption immobilization of Candida rugosa lipase onto aluminosilicate supports as biocatalysts for fatty acid sugar ester syntheses - Zaidan, Uswatun Hasanah (2011)
Nowadays, the industrial applications of the biocatalysts have not yet reached a significant level of use due to the high cost, instability and the inconvenience of separating, recycling and reusing of the enzymes. These deficiencies have motivated researchers to improve their catalytic properties by immobilization of enzymes onto selected supports. The high cost of popular supports such as calcium carbonate, rice husks and rice straw or kaolin causes many to search for cheaper substitutes from the natural environment. Instead of these alternatives, feldspar and mica appear to be most attractive since they are naturally available and have the potential to be used as low cost sorbents. In this study, aluminosilicates of feldspar and mica originated from the quary area of Tanah Putih, Gua Musang, Kelantan (Malaysia) were used as enzyme supports. They were found to have high surface area, large porosity and good mesoporous properties. Mica was hysically modified either by acid treatment,grafting with Amino-, Octyl-, Vinyl-, Mercapto- and Glycidoxy-triethoxysilanes, and activation of pre-treated support with glutaraldehyde (Glu). The modified mica preparations were used for immobilization of lipase from Candida rugosa (CRL) and exhibited improved specific activity as compared to the free enzyme by 1.8 - 2.4 folds. Lipase immobilized on mica showed enhanced protein loading (up to 8.2 mg protein/g support) and immobilization (up to 78%)compared to the free lipase (Free-CRL) and those immobilized on unmodified mica. However, another two new approaches of enzyme-aggregate-coating (EAC-CRL) and nanoscale-enzyme-reactor (NER-CRL) were found to perform higher specific activities of about 2.6 folds. The selected immobilized lipases were then used in the esterification reaction to optimize the reaction conditions factors. Optimal production conditions (83%)for the synthesis of fatty acid sugar esters (FASEs) were achieved after 48 hours with the use of capric acid (C10) and lactose sugar as substrates at temperature of 55 °C. In addition, substrates molar ratio of 1:2 (capric acid to lactose) exhibited the highest ester conversion in acetone which was the best solvent used. On the other hand, the operational stability with half lives of over 13, 10, 7 and 6 reaction cycles for NER-CRL, Amino-CRL, EAC-CRL and GluAmino-CRL, respectively, indicated the efficiency of the immobilization process. The best performance by the immobilized lipase, in terms of both activity and stability was achieved by NER-CRL, which was prepared through immobilization using the combination of physical adsorption and cross-linking approaches of lipase on unmodified mica support. The formation of lactose caprate from lactose sugar (Lac) and capric acid (CA)using biocatalysts were also evaluated through a kinetic study. Determination of the apparent kinetic parameters of Km and Vmax by means of Michaelis-Menten kinetic model was used. The Ping-Pong Bi-Bi mechanism with one substrate inhibition was adopted as it best explained the experimental findings. The kinetic results showed lower Km values (CA = 14.5 mmol/L.mg); Lac = 9308 mmol/L.mg) of the NER-CRL when compared to the Free-CRL, indicating a higher affinity of the NER-CRL towards the both substrates (Km,app (CA, Lac) < Km (CA, Lac)), thus yielding an increase in reaction rate. The kinetic parameters deduced from this model were used to simulate the initial rate data, which was in excellent agreement with the experimental values. The physicochemical properties of synthesized FASEs product of lactose caprate have been studied in order to meet their potential as high value-added biosurfactants. The present study had shown that Candida rugosa lipase immobilized on natural and low cost mica support was successfully employed as potential biocatalyst for FASEs syntheses. Furthermore, immobilized lipase preparations were able to enhance the productivity and stability, suggesting that the preparations are more versatile and adaptable for FASEs production as potential biosurfactant in industrial applications.